A Comparison of Portable Ultrasonography and the Fluoroscopy for Evaluating Medial Ankle Instability: A Cadaveric Study. Issue 1 (January 2022) - Saengsin, Jirawat; Sato, Go; Sornsakrin, Pongpanot; Lubberts, Bart; Waryasz, Gregory R.; Guss, Daniel; DiGiovanni, Christopher W.
Category: Ankle; Trauma Introduction/Purpose: Diagnosis of destabilizing deltoid ligament injuries remains challenging and is best identified with dynamic imaging techniques. This study aims to assess and compare medial clear space (MCS) distances in various stages of sequentially created supination external rotation (SER) ankle injury model using portable ultrasound (P-US) and fluoroscopy. We hypothesize that there is a strong correlation between the P-US and fluoroscopic measurements for the assessment of medial ankle instability in SER type ankle injury during the gravity stress test (GST), weight-bearing, or external rotation stress test. Methods: Ten cadaveric specimens were used for assessing medial ankle instability. The assessment was performed with all structures intact, and later with sequential transection of the anterior inferior tibiofibular ligament (Stage I), fibular (Weber-B fracture) (Stage II), posterior inferior tibiofibular ligament (Stage III), superficial deltoid ligament (Stage IVa), and deep deltoid ligament (Stage IVb). In all scenarios, the GST, external rotation stress test(45N), and Simulated weight-bearing condition(750N) were performed. The P-US measurement of the MCS was assessed at the anteromedial and inferomedial aspect of the ankle joint. Three different MCS distances were measured, as demonstrated in Figure 1. The fluoroscopic MCS measurements were assessed on a true mortise ankle view achieved during each loading condition. Spearman rank correlation was used to investigate the relationship between the P-US and fluoroscopic measurements. The inter- and intra-observer agreement was assessed using the intraclass correlation coefficient (ICC) through a two-way mixed-effects model with absolute agreement. Results: The P-US and fluoroscopic assessed medial ankle instability values during the GST, weight-bearing, and the external rotation stress test increased as the SER ankle injury stage progressed. The P-US values measured during all stress tests demonstrated a moderate to strong positive correlation with those measured with the fluoroscopy (Spearman's rank correlation ranged from 0.61-0.93, p-values <0.001). Inter-rater (P-US: 0.97, 95%CI: 0.96-0.98) and intra-rater reliability (P-US, 0.95, 95%CI: 0.94-0.96) for the P-US measurements were all substantial. Conclusion: The use of dynamic P-US to measure the MCS appears to be a reliable and repeatable technique. The P-US MCS measurement values measured in the SER ankle injury model during the GST, weight-bearing and the external rotation stress test are well correlated with those values measured with fluoroscopy. Therefore, the dynamic P-US with stress examination of the ankle has the potential to quantify medial ankle instability in a radiation-free, non-invasive, low cost, and point of care setting.